Tourism, Recreation and Sustainability (2nd Edition) Linking Culture and the Environment - McCool, Stephen F (CABI, 2014)
The growing, even accelerating, concerns about the status of the world environment initially triggered by such publications as Rachel Carson’s Silent Springand the Club of Rome Report (Meadows et al., 1972) were coalesced by the Brundtland Commission’s Our Common Futurewhich argued that survival of the human species depended on adoption of a new paradigm of economic development termed ‘sustainable development’ (World Commission on Environment and Development, 1987). This paradigm was significantly different from previous calls for environmental protection and economic progress in the sense that it represented a combination of both while attending to quality-of-life needs. The Commission argued that the only effective method of protecting the environment, addressing economic progress, alleviating poverty and preserving human rights was through a developmental paradigm that ‘provided for the needs of the present while ensuring that options for the future were preserved’.